Aproximación al análisis de una economía monástica: Santa María de Sandoval (1800-1835) (Estudios humanísticos. Geografía, historia y arte, 1994)
We're trying to analise as a whole the questions posed by the transition of ownership from the Ancient Regime to the new liberal century. To do this we delve finto a reality which comes before the revolution -the organisation of land which is the property and manor of a monastery- and, at the same time,into the legal transformations which bring, and facilitate, a different situation, it which the Church emerges as the most affected estate, losing its judicial powers, its financial system and its patronage.